The effect of thyroid disorders on obstetric and perinatal outcomes: an observational retrospective study in a tertiary care center of north India - Sharma, Ankita; Pandita, Kanik; Khajuria, Utkarsha; Chowdhary, Shazia (International Journal Of Community Medicine And Public Health, 2024)
Background: The incidence of hypothyroidism in pregnancy is between 0.5-3.5%, hyperthyroidism occurs in about 0.2-0.4%. They are associated with various maternal-fetal complications. Methods: This retrospective observational cohort study was conducted in SMGS Hospital, Jammu, India after ethical clearance. Admitted patients were included over a period of 1 year from January to December 2021. Inclusion criteria was women belonging to any period of gestation admitted to the labour room and woman with established thyroid disorder. Exclusion criteria was women on drugs influencing thyroid functions. Results: 1641 (10.43%) of 15722 women had thyroid disorders. Hypothyroidism in 10.37% (8.99% subclinical and 1.37% overt) and hyperthyroidism in 0.06%. PPROM was seen in 5.9% subclinical, 2.7% overt hypothyroid, none of hyperthyroid group. 7% subclinical, 8.5% overt hypothyroid and 1/10 women in hyperthyroid group had GDM. Abruption seen in 2.5% subclinical, 1.7% overt hypothyroid and none in hyperthyroid. In subclinical group 3.2% had gestational hypertension, 5.2% had preeclampsia and 0.6% had eclampsia. In overt hypothyroid, 2.8% had gestational hypertension, 7.9% preeclampsia and 1.7% eclampsia. In hyperthyroid group, 1/10 had gestational hypertension, 1/10 had preeclampsia. 18.2% subclinical, 14.7% overt hypothyroid, 2/10 in hyperthyroid group had history of abortion. 7% subclinical, 9.6% overt hypothyroid and 0/10 hyperthyroid group had infertility. 25.8% babies born were abnormal in terms of less gestational age at birth, low birth weight, IUGR, low apgar and IUD. 16.5% babies that had low birth weight <2.5 kg. Conclusions: The impact of thyroid disorders warrants routine screening for thyroid dysfunctions in all women in prenatal and antenatal period to predict and prevent adverse maternal-neonatal outcomes.